Antibiotic Resistance in Cases of Bacterial Meningitis: Literature Review - Warihan Unok; Ratna Devi; Fanindya Hadamu; M. Sabir Mangawing; Ary Anggara (Promotif : Jurnal Kesehatan Masyarakat, 2024)
Introduction: Meningitis is an infectious disease that attacks the cerebral membrane or swallows. Meningite is among the ten most dangerous diseases in the world. The disease can affect both children and adults. The cause of this disease can be bacteria, viruses, fungi, or aseptic. Most cases of viral meningitis usually heal themselves and are not fatal, but in severe cases, such as bacterial, biased, life-threatening. Methods: Articles related to bacterial meningitis taken from databases like Google Scholar, Pubmed and Portal Garuda over the last 5 years (2020- 2024). Use keywords: "Bacterial meningitis", "symptoms", "therapy", "antibiotic resistance Results: Based on studies that have been carried out, antibiotic resistance rates in cases of bacterial meningitis are very high and vary. Streptococcus pneumonia as one of the most common causes has high levels of resistance to antibiotics of the penicillin group. Conclusion: With the growing number of rapid, reliable and accurate diagnostics and follow-up examinations, it can cope with the incidence of antibiotic resistance in bacterial meningitis.